The research experience : planning, conducting, and reporting research - Devlin, Ann Sloan, 1948- (Thousand Oaks Sage, 2021)
"The Research Experience: Planning, Conducting and Reporting Research, Second Edition give students a complete resource to guide them through the research process. Students learn best by doing, so by presenting research in the order of an actual research project, students will absorb and apply the material more easily to their own research"--
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Methodology; Psychology -- Research -- Methodology